(untitled) (AWKA JOURNAL OF ENGLISH LANGUAGE AND LITERARY STUDIES, 2024)
There has been a conflict in the human body over what is supposed to be versus what is seen. The generally accepted notion of what it must be has become the societal norm. Any other physical structures of the human body that are against or not under the umbrella of normalcy are incomplete being, unproductive, unimportant and inhuman in society. Hence, this wrong social mapping has affected their fictional representations over centuries. Recently, scholars have observed that works of art of this present century depict different view that contradicts man’s opinion. Therefore, this study examines re-(re)portraying bodies in twenty-first-century imaginaries: a study of R. J. Palacio’s Wonder. This qualitative research seems not to have been examined which justifies its investigation. Disability literary theory that projects and instigates capabilities in impaired individuals is adopted as its theoretical framework. The textual analysis of the study finds out that the bodies (facial distortion) of August Pullman also called Auggie is re-(re)portrayed by defying societal ideals. Conclusively, the literary writer deconstructs social ideologies of bodies through the handicapped potentials to re-(re)present bodies.